2015
DOI: 10.1007/s11745-015-4007-y
|View full text |Cite
|
Sign up to set email alerts
|

Using Sterol Substitution to Probe the Role of Membrane Domains in Membrane Functions

Abstract: Ordered membrane lipid domains rich in sphingolipids and sterols (“lipid rafts”) are thought to be important in many biological processes. However, it is often difficult to distinguish domain‐dependent biological functions from ones that have a specific dependence on sterol, e.g. are dependent upon a protein with a function that is dependent upon its binding to sterol. Removing cholesterol and replacing it with various sterols with varying abilities to form membrane domains or otherwise alter membrane properti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 98 publications
0
12
0
Order By: Relevance
“…Similarly, structural differences in various sterol structures, such as the 3-hydroxyl group, the location of double bonds, aliphatic side chain, and flatness, can all affect the membrane biophysical properties and membrane order (17). Although ergosterol is the major membrane sterol in fungi, recruitment of altered sterol intermediates (minor sterols) into the membrane could significantly alter membrane order (84). Considering the fact that GlcCer(d19:2/18:0h) and several sterol structures are the most argued lipids for their role in virulence, in vitro studies using synthetic vesicles may shed light on their role in membrane physical properties (84)(85)(86)(87).…”
Section: Comparative Analysis Of Glccer and Sterols Of Other Cryptocomentioning
confidence: 99%
“…Similarly, structural differences in various sterol structures, such as the 3-hydroxyl group, the location of double bonds, aliphatic side chain, and flatness, can all affect the membrane biophysical properties and membrane order (17). Although ergosterol is the major membrane sterol in fungi, recruitment of altered sterol intermediates (minor sterols) into the membrane could significantly alter membrane order (84). Considering the fact that GlcCer(d19:2/18:0h) and several sterol structures are the most argued lipids for their role in virulence, in vitro studies using synthetic vesicles may shed light on their role in membrane physical properties (84)(85)(86)(87).…”
Section: Comparative Analysis Of Glccer and Sterols Of Other Cryptocomentioning
confidence: 99%
“…By sterol substitution, sterol structure and membrane properties can be varied under conditions such that total membrane lipid is more-or-less constant. This raises the possibility that replacing membrane cholesterol with different sterols might define when ordered domains are involved in biological functions (Xu and London, 2000), and a number of such studies have been carried out (as recently reviewed Kim and London, 2015). There are several ways to alter membrane sterol without changing sterol levels.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, dps Δ was more sensitive than the wild type to AmB and rarely grew in the presence of 2 μg/ml AmB ( Figure 4B ). The data demonstrated that the growth status of dps Δ worsened under external stress, which may be due to a disruption of the sterol biosynthesis pathway ( Kim and London, 2015 ; Gold et al, 2016 ).…”
Section: Resultsmentioning
confidence: 95%
“…Sterols have been extensively studied because of their important roles in drug resistance, developmental regulation, cell signaling, and cell growth. Therefore, a large number of sterols isolated from bacteria, fungi, and plants have been reported and researched ( Kim and London, 2015 ; Lamberson et al, 2017 ; Rivas-Marin et al, 2019 ; Ruan et al, 2019 ). Some sterols have even been implicated in human diseases, including Alzheimer’s disease and cancers ( Liu Z. et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%